PRE-HOSPITAL EMERGENCY SKILLS FOR MEDICAL STUDENTS. Issue 12 (23rd November 2015) - Wheeler, C
Abstract : Objectives & Background: There is an expectation amongst Doctors and the public that Doctors should be able to assist in medical and traumatic emergencies in the community. It is also a requirement of the General Medical Council that Doctors offer assistance. Pre-hospital care receives little attention in the majority of medical courses in the UK. At Manchester Medical School there is opportunity to study and gain experience in basic pre-hospital care for only a few students pursuing student selected modules. The aim of this study is to assess competence and confidence of medical students when dealing with pre-hospital emergencies. Methods: All of the 115 students from the 3rd year medical students based at Manchester Royal Infirmary were asked to complete a questionnaire. Confidence with pre-hospital scenarios was assessed with Likert scale questions and competence was assessed using multiple choice questions. Results: Confidence 67% of participants reported they would be willing to try to approach the scene of an accident. Airway and cervical spine control, and motorcycle helmet removal received low confidence with 45% and 74% respectively reporting feeling really anxious or not very confident. Assessment of breathing had high levels of confidence with 61% reporting quite or very confident in this skill. Control of haemorrhage received average confidence (50%). Competence The majority of students answered "Get help" for the scene approach question but only 33% assessed danger of the scene first. The immobilisation question was answered well with 82% of participants correct. There were relatively poor results for the questions regarding catastrophic haemorrhage and airway control with only 48% and 57% respectively answering correctly. Over 90% would be interested in attending a session focussed on pre-hospital care but relatively few have actually come across an incident where they were required to offer assistance. Conclusion: These results show that there is some anxiety amongst students about being able to manage pre-hospital emergencies in which the public might expect them to cope or in which they feel obliged to help. The results show that although students would be willing to help they may not posess the necessary knowledge to do so. They show that there is a demand for teaching focussed on these skills but that there is not necessarily a need for it taking into account the frequency of incidents encountered. A trial teaching programme will take place in July.